Transformation of Health Law in Indonesia After Law No. 17 of 2023: A Qualitative Study of the Protection of Patients' Rights and Responsibilities of Medical Personnel - Dahlan, Rudiyanto; Budiarsih, Budiarsih (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
This article discusses the implementation of Law No. 17 of 2023 on Health in Indonesia by highlighting aspects of patient rights protection and professional responsibility of medical personnel within the framework of restorative justice. Using a qualitative approach through exploratory case studies, data were obtained from document studies and semi-structured interviews with doctors, nurses, and health officials in three provinces. The results revealed that there was limited understanding of patient rights and the substance of restorative justice, non-uniform implementation of regulations across regions, and weaknesses in internal mediation procedures in many health facilities. In addition, there is unequal access to legal information and blurred lines of responsibility between service providers and financing institutions such as BPJS. This study concludes that the success of health law reform is not only determined by progressive regulations, but also by institutional readiness, central-local policy harmonization, and the participation of professional organizations. The findings provide theoretical contributions in strengthening restorative justice discourse in health law, as well as practical and managerial implications for the government, healthcare institutions, and medical professional actors.